Dysfunction of Akt/FoxO3a/Atg7 regulatory loop magnifies obesity-regulated muscular mass decline - Yang Yu; Jing Yang; Lixia Zheng; Han Su; Sunrun Cao; Xuehan Jiang; Xiyan Liu; Weiwei Liu; Zhuo Wang; Fang Meng; Hongde Xu; Deliang Wen; et al. (Elsevier, 2024)
Background: Myoprotein degradation accelerates in obese individuals, resulting in a decline in muscular mass. Atg7 plays a crucial role in regulating protein stability and function through both autophagy-dependent and independent pathways. As obesity progresses, the expression of Atg7 gradually rises in muscle tissue. Nonetheless, the precise impact and mechanism of Atg7 in promoting muscle mass decline in obesity remain uncertain. The study aimed to elucidate the role and underly mechanism of Atg7 action in the context of obesity-induced muscle mass decline. Methods: In this study, we established a murine model of high-fat diet-induced obesity (DIO) and introduced adeno-associated virus delivery of short hairpin RNA to knock down Atg7 (shAtg7) into the gastrocnemius muscle. We then examined the expressions of Atg7 and myoprotein degradation markers in the gastrocnemius tissues of obese patients and mice using immunofluorescence and western blotting techniques. To further investigate the effects of Atg7, we assessed skeletal muscle cell diameter and the myoprotein degradation pathway in C2C12 and HSkMC cells in the presence or absence of Atg7. Immunofluorescence staining for MyHC and western blotting were utilized for this purpose. To understand the transcriptional regulation of Atg7 in response to myoprotein degradation, we conducted luciferase reporter assays and chromatin immunoprecipitation experiments to examine whether FoxO3a enhances the transcription of Atg7. Moreover, we explored the role of Akt in Atg7-mediated regulation and its relevance to obesity-induced muscle mass decline. This was accomplished by Akt knockdown, treatment with MK2206, and GST pulldown assays to assess the interaction between Atg7 and Akt. Results: After 20 weeks of being on a high-fat diet, obesity was induced, leading to a significant decrease in the gastrocnemius muscle area and a decline in muscle performance. This was accompanied by a notable increase in Atg7 protein expression (p < 0.01). Similarly, in gastrocnemius tissues of obese patients when compared to nonobese individuals, there was a significant increase in both Atg7 (p < 0.01) and TRIM63 (p < 0.01) levels. When palmitic acid was administered to C2C12 cells, it resulted in increased Atg7 (p < 0.01), LC3Ⅱ/Ⅰ (p < 0.01), and p62 levels (p < 0.01). Additionally, it promoted FoxO3a-mediated transcription of Atg7. The knockdown of Atg7 in the gastrocnemius partially reversed DIO-induced muscle mass decline. Furthermore, when Atg7 was knocked down in C2C12 and HSkMC cells, it mitigated palmitic acid-induced insulin resistance, increased the p-Akt/Akt ratio (p < 0.01), and reduced TRIM63 (p < 0.01). Muscular atrophy mediated by Atg7 was reversed by genetic knockdown of Akt and treatment with the p-Akt inhibitor MK2206. Palmitic acid administration increased the binding between Atg7 and Akt (p < 0.01) while weakening the binding of PDK1 (p < 0.01) and PDK2 (p < 0.01) to Akt. GST pulldown assays demonstrated that Atg7 directly interacted with the C-terminal domain of Akt. Conclusion: The consumption of a high-fat diet, along with lipid-induced effects, led to the inhibition of Akt signaling, which, in turn, promoted FoxO3a-mediated transcription, increasing Atg7 levels in muscle cells. The excess Atg7 inhibited the phosphorylation of Akt, leading to a cyclic activation of FoxO3a and exacerbating the decline in muscle mass regulated by obesity. Consequently, Atg7 serves as a regulatory point in determining the decline in muscle mass induced by obesity.